PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI (Pelanggan Toko Grosir Mursid) - Margono, Supayitno & Sutarno (Universitas Slamet Riyadi, 2016)
This study aims to analyze (1) the effect of service quality on customer satisfaction (2) impact of service quality on customer loyalty (3) the impact of customer satisfaction on customer loyalty (4) impact of service quality on customer loyalty mediated by customer satisfaction. The study population was all subscribers Grocery Store Mursid in Boyolali with a sample of 100 respondents. Data collection technique used questionnaire that through stages of testing the validity and reliability first. Test requirements regression using classic assumption test. Data were analyzed using path analysis. Based on the validity of the test showed that all valid instrument and of the reliability test showed all instruments reliable. Classic assumption test results show that the variable data of this study has been to meet the assumptions required by multiple linear regression model that does not happen multikolinearitas problem, does not occur heteroskedastisitas, and autocorrelation, and residual normal. The conclusion from the results of testing each hypothesis shows that all hypothesis can be accepted or proven true, except for the hypothesis (2) impact of service quality on customer loyalty in Boyolali Mursid Wholesale Stores that can not be substantiated.Keywords: service quality, customer satisfaction, customer loyalty